Přemysl Mácha (ed.): Lighting the Bonfire, Rebuilding the Pyramid. Case Studies in Identity, Ethnicity and Nationalism in Indigenous Communities in Mexico.: Ostrava: Ostravská univerzita 2009, 184 pp. - Halbich, Marek (Lidé města, 2010)
A review of the book by Přemysl Mácha.